32 Facial Danger Zones (Dermatology Fundamentals, 2026)
Understanding surgical anatomy is crucial to performing safe surgery and avoiding complications with fillers and neuromodulators. Classically, we are taught two-dimensional face and neck anatomy. However, we now realize the key to safety when operating or injecting is to learn three-dimensional anatomy; the plane where nerves, vessels, and structures reside; and their relationship to each other. Although variations in skin thickness, subcutaneous fat, superficial facial fascia (superficial musculoaponeurotic system [SMAS]), sub-SMAS fat, and deep fascia will vary with age, location, and between individuals, the relative depth of the layers of the face remains consistent.
Keywords: dermatology; fundamentals; kamath; facial danger zones; facial nerve injury; vascular danger zones; filler vascular risks